Elevation of pro‑inflammatory and anti‑inflammatory cytokines in rat serum after acute methamphetamine treatment and traumatic brain injury - Kobeissy, Firas H. Kobeissy; Shakkour, Zaynab; El Hayek, Samer; Mohamed, Wael Mohamed Yousef; Gold, Mark S.; Wang, Kevin K. W. (Springer Nature, 2021)
The use of methamphetamine (METH) is a growing worldwide epidemic that bears grave societal implications. METH is known to exert its neurotoxic effects on the dopaminergic and serotonergic systems of the brain. In addition to this classical studied mechanism of damage, findings from our laboratory and others have shown that acute METH treatment and mechanical injury, i.e. traumatic brain injury (TBI), share common cell injury mechanism(s). Since neuro-inflammation is a signature event in TBI, we hypothesize that certain cytokine levels might also be altered in rat brain exposed to an acute METH insult. In this study, using a cytokine antibody array chip, we evaluated the serum levels of 19 cytokines in rats 24 h after exposure to a 40 mg/kg acute regimen of METH. Data were compared to rats subjected to experimental TBI using the controlled cortical impact (CCI) injury model and saline controls. Sandwich ELISA method was used to further validate some of the findings obtained from the antibody cytokine array. We confirmed that three major inflammatory-linked cytokines (IL-1β, IL-6, and IL-10) were elevated in the METH and TBI groups compared to the saline group. Such finding suggests the involvement of an inflammatory process in these brain insults, indicating that METH use is, in fact, a stressor to the immune system where systemic involvement of an altered cytokine profile may play a major role in mediating chemical brain injury after METH use.